Economic Evaluation of Livestock around Ranthambhore Tiger Reserve - Toshniwal, Ankit R.; Rasal, Vishal; Khandal, Dharmendra; Dhakad, Meenu (Indian Forester, 2021)
The present study assess the economics of livestock keeping around Ranthambhore Tiger Reserve (RTR).There are 165.64 cattle, 168.56 buffaloes and 860 goats per thousand people in and around RTR. The various cost components were identified under gross cost and net return were calculated accordingly. The study found that livestock productivity is low and highly subsidized by the free fodder from RTR forest. Grazing cost accounted for most of the expenditure in livestock which is borne by forest.